Different measures of volatility: the hypothesis of output composition in Portugal - Fuinhas, José Alberto; Marques, António Cardoso (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
This paper focuses on analyzing the impact of the consequences of monetary union on GDP volatility in Portugal. Using quarterly data from 1978:01 to 2009:04, we test the output composition effect and the correlation effect through three alternative approaches of volatility: year on year, quarter on quarter and the value of output gap. Results support the presence of the composition effect. Overall, the average covariance has played a relevant role in lowering volatility. Evidence also indicates that there is a regime shift near the years 1992-3, while both European Union membership and participation in the euro area contribute towards smoothing the economy. The decreasing path of volatility was slightly reversed after the country became a euro area member
Argumenta Oeconomica, 2011, Nr 2 (27), s. 37-64
Keywords: macroeconomic volatility; output composition effect; correlation effect; Unia Gospodarcza i Walutowa; produkt krajowy brutto; PKB; zmienność; strefa euro; korelacja